Diferentes niveles de expresión de ALDH1A1 y DYRK1B en pacientes con glioblastoma multiforme y su tiempo de sobrevida. - Sánchez-Hernández, L.; Saavedra-Sotelo, R.; Torres-Corona, D. D.; Aguirre-Quezada, D. E.; Gómez-García, E. M. (Revista Bio Ciencias, 2020)
Glioblastoma multiforme is the most malignant form of central nervous system astrocytoma. The overall survival median in patients with glioblastoma is 12 to 16 months after undergoing resection surgery, chemo radiotherapy and adjuvant treatment; However, it is still not clear what molecular factors are involved in the determination of overall survival. Recent reports show a specific isoform of aldehyde dehydrogenase (ALDH1A1), a protein that participates in cellular metabolic processes, as a potential biomarker in glioblastoma. In this study, we identify, and evaluate the expression of ALDH1A1 in biopsies of glioblastoma from Mexican patients, using immunohistochemical dyes, reverse transcription polymerase chain reaction (RT-PCR) and mass spectroscopy analyses. On the other hand, we also use immunohistochemical detection to analyze the presence of DYRK1B, a kinase involved in the regulation of tumor progression and in the regulation of the cell cycle. The purpose of this study was to investigate whether the histological expression, as well as the expression pattern of both protein ALDH1A1 and DIRK1B had a relevant correlation with overall survival of glioblastoma patients. We found different expression patterns and observed that both ALDH1A1 and DYRK1B have expression patterns that are very similar to each other and show an important correlation with the overall survival of patients. These findings allow us to consider the expression levels of ALDH1A1 and DYRK1B as possible prognostic factors in the diagnosis, or possible biomarkers for survival time in patients with glioblastoma.